A comparative assessment of microwave-based methods for moisture content characterization in stone materials. (January 2018) - Piuzzi, Emanuele; Cannazza, Giuseppe; Cataldo, Andrea; De Benedetto, Egidio; De Giorgi, Lara; Frezza, Fabrizio; Leucci, Giovanni; Pisa, Stefano; Pittella, Erika; Prontera, Santo; Timpani, Fabrizio
Highlights: Two types of Cultural Heritage stones ( gentile and leccese ) were characterized. Different methods were comparatively used for water content of stone materials. Three probes were comparatively used to infer the water content/permittivity relation. Abstract: In this work, the dielectric permittivity of pietra gentile and pietra leccese (two kinds of stone typically found in Cultural Heritage structures of Southern Italy), for different levels of moisture content, was characterized. Measurements were carried out by comparatively using three different probes as sensor (i.e., a patch resonator; an open-ended coaxial probe; and a standard WR90 waveguide) for increasing values of water content. Measurements were performed using a vector network analyzer and a time-domain reflectometer. The obtained laboratory results can be used to derive moisture content/relative dielectric permittivity calibration curves that could be employed, in practice, for noninvasive on-the-field moisture monitoring of pietra gentile - and pietra leccese -made Cultural Heritage structures.